Analisis Pengaruh Kualitas Produk dan Brand Image terhadap Keputusan Pembelian Minuman Kekinian Haus di Galuh Mas Karawang - Supyan Assauri; Budi Kramadibrata (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research aims to investigate the influence of product quality and brand image on consumer purchasing decisions for contemporary beverage products, Haus! in the Karawang area. The three main problems that are the focus of this research are: consumer preferences that are more inclined towards contemporary beverage products other than Haus!, lack of optimization of promotions for Haus! compared to other competitors, so that the brand image of Haus! not yet well known among the public, and changes in consumer tastes due to innovations in similar contemporary beverage products, which reduce the tendency to buy Haus! in the Karawang area. This research was conducted using a quantitative approach with a sample size of 247 respondents. The instrument used by researchers is a questionnaire. Quality testing of the instruments used by researchers is validity and reliability testing. The data analysis method in this research uses multiple linear regression with the help of the SPSS application. The test results show that respondents strongly agree that product quality and brand image have a significant influence on purchasing decisions. The conclusion of this research is that product quality and brand image influence the decision to purchase thirst drink products! In Galuhmas Karawang.